Codevelopment in Spain: possibilities and challenges - Pacheco Medrano, Karina (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
This article discusses the possibilities and challenges for an effective implementation of codevelopment policies in Spain. In this sense, it underlines the need for involving the immigrants themselves in the design of these policies and draws the main features of codevelopment, a concept yet imprecise which links immigration and cooperation for development in a way that intends to optimize the contribution of immigrants to their countries of origin, to the countries of destiny, as well as the potential of their bi-cultural citizenship when carrying out integration mechanisms in reception countries.
Keywords: codevelopment; cooperation for development; immigration; immigrant’ participation.